The influence of deformation texture on nucleation and growth of cube grains during primary recrystallization of AA1050 alloy. (1st May 2017) - Miszczyk, M.M.; Paul, H.; Driver, J.H.; Poplewska, J.
Abstract: The influences of microstructure and texture on the early stages of recrystallization of a commercial AA1050 alloy have been characterized with particular attention to cube grain formation. Samples were deformed along two deformation modes to form different as-deformed texture components and then lightly annealed: one group was plane strain compressed (PSC) in a channel-die, whereas the second group was deformed by equal channel angular extrusion (ECAE). The textures were measured by X-ray diffraction and SEM/EBSD. After both deformation modes a very weak residual cube texture component was observed in the samples. Cube-oriented grains were not formed during annealing of the ECAE samples whose main as-deformed texture components were close to 124<651>. During recrystallization these transformed to two components of ∼100<011> and ∼221<114>-type essentially by <110> rotations. Cube grains were extensively formed only during annealing of PSC samples. They were situated preferentially inside or in between the S-oriented deformed areas with local misorientations about <111> axes. Graphical abstract: An example of a near-cube band which grows out as a cube grain into near S-oriented neighbours. This clearly requires some form of cube grain re-orientation during initial growth, probably by the coordinated movement of dislocations. (a) Microstructure of the layer and the corresponding 111 pole figure showing (b) the orientations measured inside the S 1 -cube layer and neighbouring S 3 - oriented layers. Dotted lines mark the S 1 -cube layer (cube band). Image